Student personality and its impact on the learning process - Hassan, Rezhna; mahmood Dzai, Abdulwahid (Humanities Journal of University of Zakho, 2020)
The teaching process is a two-way process between two sides, one of them is a teacher and the other is a student, and both of them complete the process. In the framework of the classroom, the teacher deals with a group of students, each of whom has his own personalities, and they are charged with different family, social and environmental education, each of whom needs special treatment. (Student personality and its impact on the educational process) The title of the study is based on the context of linguistic psychology, and it is based on an analytical and descriptive approach. In this study two sample teaching processes were taken and recorded. The study aims to answer some questions, including: (What is the role and importance of psychology in the teaching process? Does the teacher have psychological experience for students in both lectures or not? What are the most appropriate and inappropriate teaching methods for learning? At the conclusion of the study, we found that the knowledge of the student’s psychology has a great impact on learning and the ability to determine appropriate methods and means for learning by the teacher. A list of sources, references and annexes is presented at the end of the study.